Exploring the Influence of Computer-Based National Examination on English Teaching Process: Voices from Indonesian EFL Teachers - Mardjuki, Moch. Said; Lubis, Arif Husein (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
Currently, the government of Indonesia has implemented a computer-based test for the national examination for secondary schools in Indonesia. It is believed that the administration of computer-based national examination (CBNE) would address some challenges related to dishonesty and validity. The present study is aimed to investigate the teachers’ perception of the implementation of CBNE and its influence on the English teachers’ teaching process. This study employed a qualitative design in which semi-structured interviews and document analysis from the English teachers’ lesson plans were done to obtain comprehensive data. The analysis results revealed that the teachers held a positive view of the implementation of CBNE because it is effective and efficient in terms of the process, security, scoring, and cost-saving. Besides, the components of the teaching process influenced by the administration of CBNE were extra class, teaching materials, teaching methods, and teaching activities. However, the implementation of CBNE still led to several challenges in terms of technical problems and a lack of computer experts. Therefore, by conducting an internship with other supporting parties, those challenges would be minimized.